IMPACT OF FISCAL POLICY ON EAST KALIMANTAN's CONSTRUCTION SECTOR GROWTH - Lubis, Adrian Kesar Pratama; Umami, Bafinatul; Kurniawati, Reny Dyah; Kartiasih, Fitri (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2025)
The Indonesian government's relocation of the national capital (IKN) from Jakarta to East Kalimantan is a strategic policy to address various challenges Jakarta faces, such as severe congestion, high population density, and natural disaster risks. Additionally, this move is expected to promote equitable development and accelerate economic growth in the eastern regions of Indonesia, which have lagged compared to Java Island. The realization of the infrastructure development budget for IKN in East Kalimantan has reached 97.50%, with the construction sector as the primary driver. This study aims to find out the general picture of the construction sector in East Kalimantan and analyze the construction sector's role through the fiscal policy of IKN infrastructure development in increasing output and employment. The method used is interregional input-output analysis. The results show that the construction sector is one of the key sectors in East Kalimantan, with an output multiplier of 1.87 and a labor multiplier of 0.003. An increase in final demand of 25.78 trillion rupiahs caused an increase in output in all sectors of the national economy of 48.32 trillion rupiahs and the absorption of 76919 workers.